Analyzing and Improving Anti-Phishing Schemes - Florencio, Dinei; Herley, Cormac (Institute of Electrical and Electronics Engineers, Inc., 2006)
The problem of phishing has attracted considerable attention recently, and a number of solutions and enhanced security measures have been proposed. We perform a detailed analysis of several anti-phishing schemes, and attacks and improvements. While several anti-phishing technologies address commonly observed phishing tactics, the space evolves rapidly, and a good prevention technique should be robust to anticipated as well as observed attacks. We present a number of attacks and techniques that might be easily employed by phishers and examine the robustness of a recently proposed password re-use anti-phishing system. We compare with other proposed phishing prevention techniques and find that it withstands several attacks that render current anti-phishing approaches obsolete and fares better in a large scale deployment than others.